The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1145/3072959.3126782
|View full text |Cite
|
Sign up to set email alerts
|

Scalable locally injective mappings

Abstract: InitializationIteration 20 Iteration 40Figure 1: A locally injective, energy minimizing parameterization of a mesh with over 25 million triangles computed with our algorithm in 80 minutes. The algorithm starts from a highly distorted locally injective initialization and in only 40 iterations, each requiring to solve a sparse linear system, it converges to a highly isometric map that is guaranteed to be free of inverted elements. AbstractWe present a scalable approach for the optimization of flippreventing ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(140 citation statements)
references
References 0 publications
3
137
0
Order By: Relevance
“…Furthermore, by exploiting the fixed Hessian approximation (i.e., independent of x) they are able to devise particularly efficient iterations. Rabinovich et al [2017] are inspired by the fast initial progress of global-local iterations and advocate the use of a reweighted Laplacian for the minimization of nonlinear energies on meshes. Their algorithm is shown to be very efficient in minimizing the energy from arbitrary feasible initializations, but it significantly slows down near an optimum, and so additional Newton iterations might be required if an accurate solution is pursued.…”
Section: Algorithm 1: Meta-algorithm For Nonlinear Optimizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, by exploiting the fixed Hessian approximation (i.e., independent of x) they are able to devise particularly efficient iterations. Rabinovich et al [2017] are inspired by the fast initial progress of global-local iterations and advocate the use of a reweighted Laplacian for the minimization of nonlinear energies on meshes. Their algorithm is shown to be very efficient in minimizing the energy from arbitrary feasible initializations, but it significantly slows down near an optimum, and so additional Newton iterations might be required if an accurate solution is pursued.…”
Section: Algorithm 1: Meta-algorithm For Nonlinear Optimizationmentioning
confidence: 99%
“…We used our analytic Hessian formula in equation (9) to efficiently compute the indefinite Hessian (by simply dropping the clamping). We observed that computation of Hessians using our analytic formulation works an order of magnitude faster than the automatic differentiation typically used for this task Rabinovich et al 2017]. Scalable Locally Injective Mappings -We implemented the approach of [Rabinovich et al 2017], wherein a modified Laplacian takes the place of the Hessian (SLIM).…”
Section: Experimental Evaluationmentioning
confidence: 99%
See 3 more Smart Citations